Regenerative entrepreneurship with a focus on the healthcare industry - Tuominen, Ada (My University, 2024)
Considering the global environmental, social and economic challenges, especially global warming and related environmental issues, actions need to be taken over all industries. It is highly important to understand the challenges, the burden posed by different industries and actions, and to recognize and innovate ways to target the challenges. To target the interconnected challenges discussed, holistics approaches such as sustainability and circularity have emerged. Recently, in the past years, the concept of regeneration and regenerative business models have also been increasingly discussed as it has been recognized that more than sustainable actions are needed. The aim of this thesis is to discuss and explore regenerative entrepreneurship based on the prior research on regenerative business and business models. Regenerative actions aim to renewal and making a net positive impact. Net positive impact is considered in all aspects – natural, cultural, social, financial, and human capital. The prior research on regenerative business and business models is considerably limited, and the definition of regenerative business model is still vague. Moreover, it has been stated that all industries should adopt regenerative thinking. This thesis focuses on the healthcare industry and what kinds of forms regenerative entrepreneurship takes in the industry. This thesis discusses businesses and entrepreneurial initiatives with regenerative aspects to their business. There are companies and concepts from hospital settings that embody regenerative principals. Some hospitals, especially those falling under the Green Hospital concept, as well as some companies focusing on medical equipment and medical waste, for example, exhibit aspects of regeneration in their activities. However, the ambiguity of regenerative business models poses challenges to recognizing and discussing the potential regenerative aspects of existing businesses.
Keywords: Regenerative business, Regenerative business models, Entrepreneurship, Healthcare